Garment consumption of selected gen Z college students in relation to fast fashion consumer practices - Baterbonia, Shaina M.; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Fast fashion employs a system of rapid garment production to constantly provide new trendy pieces, which consequently resulted to consumers growing accustomed to heightened purchase habits and led to excessive consumption and buildup of garment waste (Cachon and Swinney, 2011). assessing how Filipino consumer behavior can be utilized for solutions to this issue would pave path for a well-educated, environmentally-concerned, responsible Filipino market. This study aimed to answer the question, "Are UP Diliman students fast fashion consumers?", specifically to describe the purchasing behavior, buying motivations and disposal habits of selected Gen Z college students from the University of the Philippines Diliman. A survey questionnaire was developed to collect the respondents' demographic profile and information regarding their garment purchasing behavior, buying motivations, and disposal habits. The data is synthesized into a fashion consumer profile, and then compared to the profile of a fast fashion consumer. The results of the study determined that the participants of the study definitely practice certain garment consumption habits that are characteristic of those fast fashion consumers, but there is a heavy presence of other elements in their consumer profile that contrast with the nature of a fast fashion consumer. There are certain disconnects in the consumer mindset of the respondents, suvh as awareness of the negative impacts of the fast fashion system and preference for ethical or environmentally conscious brands with the actual garment consumption activities they apply, which lean towards overconsumption and ecologically unsustainable disposal habits. Information from this study may supplement further research, such as the development of a framework with a quantified method of scoring units in the analysis of a garment consumer profile, studies on other factors that influence existing consumer habits, and studies on the correlation of certain fast fashion mindsets and consumption activities. All these would contribute to the pursuit of knowledge for better and more efficient ways to market ecological and ethical alternatives to fast fashion consumers, particularly those under the demographic of Filipino, Gen Z college students.
Available to the general public.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman
Keywords: Fashion -- Philippines -- Quezon City; College students as consumers -- Philippines -- Quezon City; College students -- Clothing -- Philippines -- Quezon City; Consumer behavior